Cloud path, journey of a wandering monk - Korea Foundation ([Seoul] Korea Foundation, 2005)
Tells of the life of an American convert to Korean Buddhism and his life as a Buddhist monk. In his quest for enlightenment, 35-year-old Hyon-Gak spends part of his year in meditation at Hwagyesa Temple in Korea. During the rest of the year, he takes the "Cloud Path," or journey without destination, a wide, ever-changing pilgrimage through the outside world where he experiences its peoples and landscapes.
In English, French and Spanish languages.
Keywords: Hyon gak -- 1964-.; Priests, Zen -- Korea (South) -- Biography; Buddhist converts -- Biography; Monastic and religious life (Buddhism) -- Korea (South).; Buddhism -- Korea (South).